GAMBARAN HARGA DIRI PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA BUDI MULIA I CIPAYUNG JAKARTA TIMUR - Oktaviolyta Cemerlang (2023)
The elderly will experience an aging process that can be seen with a decrease in physical abilities. This will cause psychological problems, one of which is a negative assessment of himself which can cause disturbances in the self-esteem of the elderly. This study aims to analyze the picture of self-esteem in the elderly at Tresna Werdha Budi Mulia I Cipayung Social Institution. This study uses a descriptive research design to describe or explain the variables studied without analyzing the relationship between variables. The sampling technique uses Total Sampling with a sample of 50 respondents. The instrument used was the Rosenberg Self-Esteem Scale (RSES) Questionnaire to measure the self-esteem of the elderly. The results of this study were the majority of elderly aged 63 years, namely 6 (12%) respondents, women as many as 27 (54%) respondents, elementary school education level 28 (56%) respondents, marital status divorced 23 (46%) respondents, number of children < 2 Children 32 (64%) of respondents, and length of stay in the orphanage ≥ 2 years 33 (66%) of respondents. Researchers suggest nursing homes to continue to maintain activities that are carried out routinely which can increase or maintain the self-esteem of the elderly who are in the orphanage.